2022
DOI: 10.35445/alishlah.v14i2.1030
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Exposition Reading Materials for Senior High School Textbook: Students’ Needs Analysis

Abstract: This research intends to dig out the Senior High School students' needs in English reading materials development based on climate change material revised by students', and teachers' views. The data were obtained by applying a questionnaire and semi-structured interviews. The data are described both quantitatively and qualitatively. The outcomes of the need analysis represent that: 1) English is important to students' future careers, (2) students’ English proficiency is at the beginner level, 3) students still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Other studies at the secondary education level focus on the development of climate change-based report texts and exposition reading materials for high school students. These studies informed us that deliberate design of supplemental textbooks and e-module which incorporated climate change issues contributed to students' awareness of climate change issues (Becce Tenridinanti et al, 2021;Mufidah et al, 2023;Noto, et al, 2022) Based on the previous related studies, it is evident that there has been a progressive focus on tackling the issues raised by climate change in educational settings. As what have been mandated in the latest curriculum which is kurikulum Merdeka in one of its characteristics, the focus is on essential, relevant, and in-depth material, allowing ample time for students to develop creativity and innovation in achieving basic competencies such as literacy and numeracy.…”
Section: Introductionmentioning
confidence: 86%
“…Other studies at the secondary education level focus on the development of climate change-based report texts and exposition reading materials for high school students. These studies informed us that deliberate design of supplemental textbooks and e-module which incorporated climate change issues contributed to students' awareness of climate change issues (Becce Tenridinanti et al, 2021;Mufidah et al, 2023;Noto, et al, 2022) Based on the previous related studies, it is evident that there has been a progressive focus on tackling the issues raised by climate change in educational settings. As what have been mandated in the latest curriculum which is kurikulum Merdeka in one of its characteristics, the focus is on essential, relevant, and in-depth material, allowing ample time for students to develop creativity and innovation in achieving basic competencies such as literacy and numeracy.…”
Section: Introductionmentioning
confidence: 86%
“…These findings are corroborated by Darmawan and Dagamac (2021) and Djalante (2018), who suggest that developers of reading materials need to increase English reading texts that address comprehensive environmental issues for secondary high schools to gain students' climate awareness and literacy. Moreover, the incorporation of reading materials on climate change should be expanded as Tenridinanti et al (2021), andNoto et al (2022) demonstrated that providing climate change-based reading materials can improve students' learning outcomes by addressing the intricate nature of the concepts and catering to their specific needs. The students' viewpoints on their present understanding of climate change are depicted in Table 5.…”
Section: Present Situation Analysismentioning
confidence: 99%
“…Despite the acknowledged need for descriptive texts on climate change in secondary high school curricula, there remains a gap in aligning these materials with the demands of the current curriculum. Most scholarly research to date, including works by Tenridinanti et al (2021) and Noto et al (2022), has focused on report and exposition texts based on previous curricula. There is a growing recognition of the need for more studies on designing syllabi and instructional materials that emphasize descriptive texts.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on climate change include work by Tenridinanti et al (2021), who explored the development of report texts based on climate change, and Noto et al (2022), who crafted exposition reading materials tailored for senior high school students. Furthermore, research has been done on the intersections of virtual drama with the theme of climate change.…”
Section: Introductionmentioning
confidence: 99%